Efficient Overproduction of Active Nitrile Hydratase by Coupling Expression Induction and Enzyme Maturation via Programming a Controllable Cobalt-Responsive Gene Circuit - Han, Laichuang; Cui, Wenjing; Lin, Qiao; Chen, Qiaoqing; Suo, Feiya; Ma, Ke; Wang, Yang; Hao, Wenliang; Cheng, Zhongyi; Zhou, Zhemin (Frontiers in Bioengineering and Biotechnology, 2020)
A robust and portable expression system is of great importance in enzyme production, metabolic engineering, and synthetic biology, which maximizes the performance of the engineered system. In this study, a tailor-made cobalt-induced expression system (CIES) was developed for low-cost and eco-friendly nitrile hydratase (NHase) production. First, the strong promoter Pveg from Bacillus subtilis, the Ni(II)/Co(II) responsive repressor RcnR, and its operator were reorganized to construct a CIES. In this system, the expression of reporter green fluorescent protein (GFP) was specifically triggered by Co(II) over a broad range of concentration. The performance of the cobalt-induced system was evolved to version 2.0 (CIES 2.0) for adaptation to different concentrations of Co(II) through programming a homeostasis system that rebalances cobalt efflux and influx with RcnA and NiCoT, respectively. Harnessing these synthetic platforms, the induced expression of NHase was coupled with enzyme maturation by Co(II) in a synchronizable manner without requiring additional inducers, which is a unique feature relative to other induced systems for production of NHase. The yield of NHase was 111.2 ± 17.9 U/ml using CIES and 114.9 ± 1.4 U/ml using CIES 2.0, which has a producing capability equivalent to that of commonly used isopropyl thiogalactoside (IPTG)-induced systems. In a scale-up system using a 5-L fermenter, the yielded enzymatic activity reached 542.2 ± 42.8 U/ml, suggesting that the designer platform for NHase is readily applied to the industry. The design of CIES in this study not only provided a low-cost and eco-friendly platform to overproduce NHase but also proposed a promising pipeline for development of synthetic platforms for expression of metalloenzymes.